2021
DOI: 10.1111/jfbc.13963
|View full text |Cite
|
Sign up to set email alerts
|

Ajwain oil attenuates allergic response of ovalbumin‐induced allergic rhinitis via alteration of inflammatory, oxidative stress, and Th1/Th2 responses

Abstract: Background: Allergic rhinitis (AR) is an immune inflammatory‐related disorder that affects the nasal mucosa. Free radicals play a crucial role in the expansion of allergic reaction and the researcher used the antioxidant therapy to treat the disease. Trachyspermum ammi L. (Ajwain oil) is popular traditional medicine. It has been proved their potential effect on various diseases. Ajwain oil showed anti‐tumor, antioxidant, antidiabetic, anti‐inflammatory, and anti‐bacterial properties. Yet, the anti‐allergic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…During the oxidative stress, increases the level of ROS, which further combine with the NO start the production of peroxynitrite (ONOO À ) and ultimately enhance the protein nitration and lipid peroxidation. 8,33 LPO induces the reduction in the membrane fluidity, diminishing of membrane function, suppress the energy production and interferes with the mitochondrial respirator chain. 36 MDA can be formed through the mechanism of lipid peroxidation, which is caused by the presence of oxygen radicals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…During the oxidative stress, increases the level of ROS, which further combine with the NO start the production of peroxynitrite (ONOO À ) and ultimately enhance the protein nitration and lipid peroxidation. 8,33 LPO induces the reduction in the membrane fluidity, diminishing of membrane function, suppress the energy production and interferes with the mitochondrial respirator chain. 36 MDA can be formed through the mechanism of lipid peroxidation, which is caused by the presence of oxygen radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Current research suggest that the increased ROS level is linked with the induction of mitochondrial dysfunction, which occur due to induction of oxidative stress in the nasal mucosa. The oxidative stress enhanced the production of sputum and mucus and also causes the injury in the lung cells 33,34 . Wang et al 8 suggest that various toxicant such as OVA causes the oxidative stress in the nasal mucosa via reduction of oxidative defense mechanism and total oxidant status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxidative stress resulting from excessive production of reactive oxygen species (ROS) has been reported to be closely correlated to the development of AR. 13,14 ROS enhances mucosa permeability and mucus production and leads to the secretion of inflammatory mediators. 15 Studies have demonstrated that the nuclear factor erythroid 2-related factor 2/heme oxygenase-1 (Nrf2/HO-1) signaling pathway plays a crucial part in oxidative stress.…”
Section: Introductionmentioning
confidence: 99%